2020
DOI: 10.1111/bcp.14440
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use and safety of ibrutinib in real‐life practice

Abstract: Aims To provide real‐life data on patterns of use and safety of ibrutinib. Methods A cohort study including all patients initiating ibrutinib between 21 November 2014 and 21 November 2018, and followed for 1 year was conducted. Patient characteristics, ibrutinib use and adverse drug reactions (ADRs) were collected from medical records. Kaplan–Meier analysis estimated the probability of developing ibrutinib‐associated serious ADRs (SADRs) with a 95% confidence interval (CI). A Cox proportional hazards model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In a recent French study on patterns of use and safety of ibrutinib in real-life practice in 102 patients, half of whom were CLL patients, the authors reported that 42.1% of patients permanently discontinued ibrutinib in the first year, mostly for progression (51.2%) or adverse drug reactions (ADRs) (32.6%), while 47.1% of patients experienced at least one ibrutinib-associated serious ADR (SADR; hematological, infectious, and vascular disorders in particular) [ 33 ]. These authors also reported the probability of developing an ibrutinib-associated SADR to be 35.1% (95% CI: 26.3-45.7) at 3 months, 44.8% (95% CI: 35.2-55.8) at 6 months, and 54.3% (95% CI: 44.0-65.2) at 12 months, further indicating a significant association of age of ≥80 years (hazard ratio [HR]: 2.03; 95% CI: 1.02-4.05) and being treated for CLL (HR: 1.81; 95% CI: 1.01-3.25) with a higher risk of SADR occurrence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent French study on patterns of use and safety of ibrutinib in real-life practice in 102 patients, half of whom were CLL patients, the authors reported that 42.1% of patients permanently discontinued ibrutinib in the first year, mostly for progression (51.2%) or adverse drug reactions (ADRs) (32.6%), while 47.1% of patients experienced at least one ibrutinib-associated serious ADR (SADR; hematological, infectious, and vascular disorders in particular) [ 33 ]. These authors also reported the probability of developing an ibrutinib-associated SADR to be 35.1% (95% CI: 26.3-45.7) at 3 months, 44.8% (95% CI: 35.2-55.8) at 6 months, and 54.3% (95% CI: 44.0-65.2) at 12 months, further indicating a significant association of age of ≥80 years (hazard ratio [HR]: 2.03; 95% CI: 1.02-4.05) and being treated for CLL (HR: 1.81; 95% CI: 1.01-3.25) with a higher risk of SADR occurrence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, comorbidity burden and co-medications could compromise the safety of ibrutinib in real-life practice. In a previously published cohort study (n 102 patients), patients aged ≥80 years were at higher risk of serious adverse drug reaction (SADR) within the first year of ibrutinib treatment (Allouchery et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib not only inhibits BTK potently and irreversibly, but it also inhibits other related Tec family kinases, and off‐target inhibition appears to contribute to specific ibrutinib toxicities. 4 , 5 It also regulates other cells of the immune system, such as receptor‐mediated phagocytosis of Candida albicans 6 , 7 in macrophages. A “net state of immunosuppression” has been proposed, which includes factors affecting the adaptive and innate immune system, disease‐related factors, aging, comorbidities, immunosuppressive drugs, and possibly a genetic predisposition as contributing to ibrutinib‐associated IFI.…”
Section: Introductionmentioning
confidence: 99%